(untitled) (Jurnal Mekanikal, 2018)
Material specification and operating temperatures are very important parameter for product performance especially for transportation application such as brake pad material. For light rail brake pad, other than strength, wear and friction, thermal stability is also an important property to investigate due to temperature variation during operation. Hence, four sample differences of laboratory formulation are used to study the thermal stability of brake pad material. The thermal characteristic is determined by thermal gravimetric and differential thermal analyser which are initially heated from 30Â°C to 1000Â°C and are used in combination with the evolved gas analysis. Scanning electron microscope equipped with energy dispersive x-ray are used to determine the element present in formulated brake pad samples. A brake pad is basically a mixture of iron (Fe), carbon (C), fibre, lubricant material and binder system. Some vapours and gases (water, carbon dioxide, methanol, phenol and ammonia) are detected which contributed to the results in the weight change of each sample. These gases are from the phenolic binder. Sample S1 shows a low percentage of weight loss and more stable product compared to other samples. The stability of product materials plays a main role in determining the thermal stability of the samples at the high temperatures.